REDUCING THE EMBRYONIC PHENOTYPE IN ERYTHROBLASTS AND MEGAKARYOCYTES DERIVED FROM HUMAN PLURIPOTENT STEM CELLS THROUGH A FORWARD PROGRAMMING APPROACH - McDonald, Rebecca (Apollo - University of Cambridge Repository, 2024)
[Restricted]
Keywords: Embryonic; Erythrocytes; Forward Programming; iPSC; Megakaryocytes; Mogrify